Poisoning cases attending emergency department in Dhulikhel Hospital- Kathmandu University Teaching Hospital - Marahatta, SB; Singh, J; Shrestha, R; Koju, R (Kathmandu University Medical Journal, 2010)
Objective: The objective of the present study is to evaluate the characteristics of acute poisoning cases admitted to emergency department over a one year period. The demographic, clinical and psycho-social aspects of the patients were analysed. Materials and methods: A hospital based study was carried out in the emergency department, Kathmandu University Teaching Hospital/ Dhulikhel Hospital, Dhulikhel analysing the data of the poisoning cases attended for one year. The study was carried out amongst inpatients attending emergency with acute poisoning. Results: A total of 54 patients were admitted to the emergency department with acute poisoning. The female-to-male ratio was 1.34:1. Most poisoning occurred in the age group of above 40 years. The mean ages of female and male were 29.87 ±14.85 years and 35.54±15.02 years respectively. By occupation 40.38% of the cases were farmers. Only 35.29% of the patients were illiterate. 79.24% of the cases intentionally consume the poison. Organ phosphorus poisoning (OP) was the most common poisoning. Oral route was the commonest route of poisoning accounting 98.1%. Sixty-six percentage (66.66%) of the cases had the poison stored in their home with 27.7% bought from the market once needed. Among the cases of acute poisoning 5.55% were fatal. Conclusion: The following conclusions were reached: (1) females were at greater risk for poisoning than males, (2) self-poisoning cases constituted the majority of all poisonings, and (3) the main agents of self-poisoning were OP poisoning. Key words: poisoning; insecticides; organophosphorus DOI: 10.3126/kumj.v7i2.2711 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26,152-156